Justiciabilidade dos direitos sociais e econômicos no o Brasil: desafios e perspectivas - Flavia Piovesan; Renato Stanziola Vieira (Araucaria)
The study of the fundamental rights must be oriented by an integral vision characterized by the indivisibility and interdependence of the classic freedoms rights and the social, economic and cultural rights. From this perspective, and in the light of the Constitution previsions of 1988, that incorporated several international treaties concerning the social rights ratified by Brazil, the study of a specific case was chosen to serve as analysis of the justiciability of the fundamental social and economic rights in Brazil. The article will study aspects like the Brazilian and international protection of the social and economic fundamental rights, how the Brazilian Supreme Court has addressed the question, and the debates, nowadays, about the outlines of Brazilian constitutional jurisdiction in search of protecting and implementation of those rights.